PRODUKTIVITAS GETAH PINUS (Pinus merkusii) PADA VARIASI UMUR, DIAMETER, DAN JUMLAH KOAKAN (Studi di RPH Sumberejo BKPH Ngadisono KPH Kedu Selatan) (Agrienvi: Jurnal Ilmu Pertanian, 2021)
The factors that influence the production of pine (Pinus mersuii) resin are an essential part of determining the behavior of resin productivity. This study aims to assess the effect of age, diameter, and number of quaree on the productivity of pine resin. The sample was taken on pine stands aged 17 years and 21 years. At each age, we choose three people of resin tapper. Twenty samples of the trees were purposively selected from each resin tapper in 26-36 cm diameter at breast height (dbh). Some quarre were counted by the tree chosen based on the dbh. Measurement of resin production was carried out three times at every ten days interval. We used multiple linear regression analysis and curve estimation. The result showed that the dbh and the number of quarre affected resin productivity. Productivity increases with the increase in dbh. Likewise, the increased number of quarre, affected to increased in resin productivity. It was seen that the 5 of the number of quarre began to decreased in resin productivity. The age of trees has not shown a significant effect. The curve between diameter and resin production tends to be linear, while the number of quarre tends to be quadratics.